Study of Alloying Process on 40Cr Surface with Electron Beam after Electroplated Cr Layer. (29th October 2013) - Hongbin, Xu; Jianjun, Hu; Hui, Li; Rongshan, Mao; Fei, Sun; Tianfeng, Hou
Abstract : The electroplated hard chromium coat was selected as precoating to improve surface properties of 40Cr. Then electron beam alloying process was experimentalized. The relation rules were summarized between alloying process parameters and overall surface properties by surface morphology observation, surface energy spectrum analysis, EDX analysis in section, and XRD. Experiment results showed that the microcracks appeared on surface of electron beam alloying specimen. Microcracks could disappear when the orthogonal experimental optimum process was used. The matrix metal elements diffused into metal coating surface after electron beam treatment. The maximum depth of alloyed layer could reach 8 μ m after electron beam alloying treatment, and electron beam alloying process generated new residual austenite phase.